On the Way to the Technological Development of Newly Selected Non-Saccharomyces Yeasts Selected as Innovative Biocontrol Agents in Table Grapes - Antonella Salerno; Margherita D’Amico; Carlo Bergamini; Flavia Angela Maria Maggiolini; Marco Vendemia; Annalisa Prencipe; Claudia Rita Catacchio; Mario Ventura; Maria Francesca Cardone; Antonio Domenico Marsico (Microorganisms, 2024)
Post-harvest decay of fresh table grapes causes considerable annual production losses. The main fungal agents of decay both in pre- and post-harvest are B. cinerea, Penicillium spp., Aspergillus spp., Alternaria spp., and Cladosporium spp. To date, the use of agrochemicals and SO2 are the main methods to control grape molds in pre- and postharvest, respectively. Significant improvements, however, have already been made in to apply innovative and more environmentally sustainable control strategies, such as Biological Control Agents (BCAs), which can reduce disease severity in both pre- and post-harvest. In this study, 31 new non-Saccharomyces yeast strains, isolated from berries of native Apulian table grape genotypes, were tested for their in vivo effectiveness against grey mold of table grapes, resulting in two St. bacillaris (‘N22_I1’ and ‘S13_I3’), one S. diversa (‘N22_I3’), one A. pullulans (‘OLB_9.1_VL’) and one H. uvarum (‘OLB_9.1_BR’) yeast strains that were marked as efficient and good BCAs. Their mechanisms of action were characterized through in vitro assays, and additional characteristics were evaluated to assess the economic feasibility and viability for future technological employment. Their effectiveness was tested by reducing the working concentration, their antagonistic effect on a wide range of fungal pathogens, their ability to survive in formulations with long shelf life, and their safety to human health.